Optimasi Pengembangan Embung di Indonesia - Budiman Notoatmojo; Rudi Rivai (The Winners, 2001)
Article performs the optimation  of embung utilization  in Indonesia, especially in NTT province. It is a descriptive using farmer as respondents who use embung as source of drinking water, irrigation, drinking water and field irrigation, as well as drinking water and farm irrigation. It is concluded that embung is a source of developing horticulture in the urban areas.